2015
DOI: 10.4049/jimmunol.1402835
|View full text |Cite
|
Sign up to set email alerts
|

H5N1 Vaccine–Elicited Memory B Cells Are Genetically Constrained by the IGHV Locus in the Recognition of a Neutralizing Epitope in the Hemagglutinin Stem

Abstract: Due to significant viral diversity, vaccines that elicit durable and broad protection against influenza have been elusive. Recent research has focused on the potential of highly conserved regions of the viral hemagglutinin (HA) as targets for broadly neutralizing antibody responses. Antibodies that bind the highly conserved stem or stalk of HA can be elicited by vaccination in humans and animal models and neutralize diverse influenza strains. However, the frequency and phenotype of HA stem-specific B cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(136 citation statements)
references
References 37 publications
11
125
0
Order By: Relevance
“…We used recombinant group 1-specific (H5) and group 2-specific (H3) HA probes – modified to prevent sialic acid binding (HAΔSA) (Wheatley et al, 2015; Whittle et al, 2014) – to co-stain and sort PBMCs isolated two weeks post H5N1 MIV boost (Figure 1C and S2). We recovered sequences of memory B cell immunoglobulin gene transcripts from six of the ten studied subjects (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used recombinant group 1-specific (H5) and group 2-specific (H3) HA probes – modified to prevent sialic acid binding (HAΔSA) (Wheatley et al, 2015; Whittle et al, 2014) – to co-stain and sort PBMCs isolated two weeks post H5N1 MIV boost (Figure 1C and S2). We recovered sequences of memory B cell immunoglobulin gene transcripts from six of the ten studied subjects (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of reproducibility, the HV1-69-derived antibodies have the additional advantage of utilizing heavy chain-only recognition, and prior studies have shown their vaccine-induced elicitation (Khurana et al, 2013; Ledgerwood et al, 2011; Ledgerwood et al, 2013; Sui et al, 2009; Wheatley et al, 2015; Whittle et al, 2014). However, HV1-69-derived antibodies generally do not neutralize both group 1 and 2 strains of influenza A, and, only a single HV1-69-derived antibody has been identified (CR9114) capable of neutralizing both group 1 and 2 strains of influenza A (Dreyfus et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of vaccination in boosting preexisting versus generating new nonNAb responses remains to be clarified. Technologies to define influenza-specific B cells and sequence their Ig genes allow a more detailed probe of preexisting versus new influenza-specific Ab responses and could be applied to non-NAb responses (42).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, binding of antibodies with this re-arrangement to the stem domain has been shown to be mediated primarily by the heavy chain with little contribution of the light chain [28]. Additionally, while many antibodies are still able to retain their binding when reverted to the V H 1-69 germline sequence, the presence of multiple V H 1-69 polymorphisms that do not bind suggests that there may be a genetic bias in the ability to mount broadly neutralizing antibody responses, with certain alleles of V H 1-69 being more favorable in producing these antibodies [30,31*]. However, human-derived broadly neutralizing antibodies that do not use the V H 1-69 gene have also been characterized, signifying that cross-reactivity is not exclusively linked to the V H 1-69 allele [22].…”
Section: Characterizing Broadly Neutralizing Antibodiesmentioning
confidence: 99%